Development of an Effective Curriculum for United Kingdom Language Learning Based on Local Wisdom - Rinovian Rais; Pratiwi Samad; Habiyah Srianah Amir; Arini Nasra; S. Sumihatu Ummah MS (International Journal of Language and Ubiquitous Learning, 2024)
Background. The development of an United Kingdom language learning curriculum that is relevant to the local context is a challenge in the world of education, especially in Indonesia which is rich in local culture and wisdom. United Kingdom language learning has tended to adopt global standards without paying attention to students' cultural backgrounds, making it less relevant for students in areas with strong cultures. In this context, the development of a curriculum based on local wisdom is expected to increase student engagement and the quality of United Kingdom language learning. Purpose. This study aims to develop an effective United Kingdom curriculum by integrating elements of local wisdom, as well as evaluating the impact of the implementation of the curriculum on students' motivation and language skills. Method. This study uses a qualitative method with a case study approach, involving five schools in rural and urban areas. Data were collected through interviews, classroom observations, and questionnaires given to 100 students and 10 teachers. Results. The results of the study show that the integration of local wisdom in United Kingdom language learning increases student motivation and participation, especially in rural areas. Students in urban areas tend to need materials that combine more local and global aspects. Teachers face challenges in finding suitable teaching materials, but in general this approach is considered effective. Conclusion. The conclusion of this study is that the curriculum based on local wisdom is able to increase the relevance and effectiveness of United Kingdom language learning. However, flexibility is needed in its application so that it can be adjusted to the needs of students in various regions.